Flours and starches made from cassava (yuca), yam, sweet potatoes and ñampi: functional properties and possible applications in the food industry - Pedro Vargas-Aguilar (Tecnología en Marcha, 2016)
A review was carried out of the physical and chemical properties of flours and starches made from cassava, yam, ñampi, and sweet potatoes. Amyloseamylopectin content, viscosity, nutritional value and fiber content were studied to associate them with their functional and technical-functional properties. A relationship was found between amylose-amylopectin, viscosity and fiber content and digestibility of those starches, as well as with glycemic index values. It was found that it is possible to introduce modifications through fermentation to enhance the nutritional value of these starches. Fermentation allows the production of gluten-free bread and energy drinks as an option to diversify products. It was also found that there is a relationship between starch viscosity and a reduction of fat absorption in fried foods.